1984
DOI: 10.1007/bf01716446
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and absolute bioavailability of diltiazem in humans

Abstract: Six healthy male volunteers received single doses of diltiazem hydrochloride on three occasions separated by at least 10 days. Modes of administration were: 10-minute intravenous infusion of a 20-mg dose; oral administration of 120 mg in solution form; and oral administration of 120 mg as two 60-mg sustained-release tablets. Diltiazem concentrations were measured by electron-capture gas chromatography in multiple plasma samples drawn during the 36 hours after dosage. Following intravenous administration, mean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

1990
1990
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(22 citation statements)
references
References 9 publications
0
22
0
Order By: Relevance
“…Response to the reported pharmacokinetic parameters of the same multiple oral dose, the present results showed that the time to maximum plasma concentration [t max = (10.39 ± 1.32) h] was prolonged significantly. However, the elimination half-life (t 1/2β = 14.38 ± 0.72 h) remained extending (Lefebvre et al, 1994;Roberts et al, 1991;Ochs et al, 1984).…”
Section: Discussionmentioning
confidence: 96%
“…Response to the reported pharmacokinetic parameters of the same multiple oral dose, the present results showed that the time to maximum plasma concentration [t max = (10.39 ± 1.32) h] was prolonged significantly. However, the elimination half-life (t 1/2β = 14.38 ± 0.72 h) remained extending (Lefebvre et al, 1994;Roberts et al, 1991;Ochs et al, 1984).…”
Section: Discussionmentioning
confidence: 96%
“…Based on preclinical data, desacetyldiltiazem is 25-50% as potent a coronary vasodilator as diltiazem, and the N-desmethyldiltiazem metabolite is about 20% as potent [24,25]. The t 1/2 of orally administered diltiazem averages about 4 h (range: 2 -11 h) in healthy volunteers [21,22]. Again, these published values for diltiazem pharmacokinetic parameters are consistent with the values found in our study, including the large coefficients of variation for C max , C min , and t 1/2 .…”
Section: Discussionmentioning
confidence: 98%
“…Diltiazem undergoes extensive first-pass metabolism after oral ingestion, with an absolute bioavailability of 40% [20][21][22]. Only 1-3% of an oral dose of diltiazem is excreted unchanged in the urine, while 35% of the dose is recovered as metabolites in the urine [20][21][22].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations